Challenges and Future Prospects of Nanoemulsion as a Drug Delivery System - Nishitani Yukuyama, Megumi; Tomiko Myiake Kato, Edna; Lobenberg, Raimar; Araci Bou-Chacra, Nadia (Current Pharmaceutical Design, 2017)
Nanoemulsion has the potential to overcome several disadvantages in drug formulation. Loading poor water-soluble drugs in the appropriate nanoemulsions enhances their wettability and/or solubility. Consequently, this improves their pharmacokinetics and pharmacodynamics by different routes of administration. Associated with the optimum nanodroplets size or even combined with key components, the droplets act as a reservoir of drugs, enabling nanoemulsion to be multifunctional platform to treat diverse diseases. A number of important advantages, which comprise nanoemulsion attributes, such as efficient drug release with appropriate rate, prolonged efficacy, drug uptake control, low side effects and drug protection properties from enzymatic or oxidative processes, have been reported in last decade. The high flexibility of nanoemulsion includes also a variety of manufacturing process options and a combination of widely assorted components such as surfactants, liquid lipids or even drug-conjugates. These features provide alternatives for designing innovative nanoemulsions aiming at high-value applications. This review presents the challenges and prospects of different nanoemulsion types and its application. The drug interaction with the components of the formulation, as well as the drug mechanistic interaction with the biological environment of different routes of administration are also presented.
Keywords: Nanoemulsion